2013
DOI: 10.1371/journal.pone.0056161
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Is Essential for Protecting against LPS-Induced Pregnancy Loss. LIF as a Potential Mediator of the Anti-inflammatory Effect of Progesterone

Abstract: Lipopolysaccharide (LPS) administration to mice on day 7 of gestation led to 100% embryonic resorption after 24 h. In this model, nitric oxide is fundamental for the resorption process. Progesterone may be responsible, at least in part, for a Th2 switch in the feto-maternal interface, inducing active immune tolerance against fetal antigens. Th2 cells promote the development of T cells, producing leukemia inhibitory factor (LIF), which seems to be important due to its immunomodulatory action during early pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 71 publications
6
76
1
1
Order By: Relevance
“…26 In the uterus of pregnant mice, LIF likely plays a similar but local role in the protective effect of progesterone against endotoxin-induced fetal demise by reducing nitric oxide levels in utero. 27 Another important gestational factor is IL-10, which is a type-2 cytokine that is expected to play a key role in pregnancy immunotolerance through the establishment of a Th2 immune response at the maternal2fetal interface. 28,29 IL-10 inhibits the production of several pro-inflammatory cytokines, including TNF-a in Mws and IFN-c in NK cells, thereby preventing the development of type-1 immune reactions that are deleterious for both the establishment and maintenance of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…26 In the uterus of pregnant mice, LIF likely plays a similar but local role in the protective effect of progesterone against endotoxin-induced fetal demise by reducing nitric oxide levels in utero. 27 Another important gestational factor is IL-10, which is a type-2 cytokine that is expected to play a key role in pregnancy immunotolerance through the establishment of a Th2 immune response at the maternal2fetal interface. 28,29 IL-10 inhibits the production of several pro-inflammatory cytokines, including TNF-a in Mws and IFN-c in NK cells, thereby preventing the development of type-1 immune reactions that are deleterious for both the establishment and maintenance of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…However, while the underlying molecular mechanisms are not fully understood, maternal plasma progesterone has been reported to be lower in LPS-induced preterm birth models (19), and unaltered by probiotics (20). H 2 may therefore be superior in this regard, as a previous study reported that progesterone exerted anti-inflammatory effects at the maternal-foetal interface and increased the proportion of decidual regulatory T cells (21).…”
Section: Discussionmentioning
confidence: 98%
“…Progesterone up regulates LIF mRNA expression in vitro [ 20 ]. Progesterone inhibits NK activity at the feto-maternal interface, inhibits the release of arachidonic acid, and favours the production of asymmetric, pregnancy-protecting antibodies.…”
Section: Action Of Progesterone On Cytokinesmentioning
confidence: 99%